2013
DOI: 10.1111/jog.12200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between placental gene expression of 11β‐hydroxysteroid dehydrogenases and infantile growth at 10 months of age

Abstract: No direct correlation was observed between the placental gene expression of 11βHSD and infantile growth at 10 months of age. However, the placental gene expression of 11βHSD-1 may be indirectly connected with infantile growth via adiponectin-associated metabolic regulation represented by adiponectin levels in umbilical cord blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Both isoforms have been found relevant to childhood obesity (Ruan et al, 2014 ), the antecedent of MetS. In interaction with adiponectin, HSD11B1 determines the metabolic rate already in utero and postnatal development (Muramatsu-Kato et al, 2014 ), in a form of ontogenetic programming. HSD11B2 (16q22) protects cells from the growth-inhibiting and/or pro-apoptotic effects of cortisol, particularly during embryonic development.…”
Section: Genomic Foundation Of Basic Regulatory Mechanisms In Metsmentioning
confidence: 99%
“…Both isoforms have been found relevant to childhood obesity (Ruan et al, 2014 ), the antecedent of MetS. In interaction with adiponectin, HSD11B1 determines the metabolic rate already in utero and postnatal development (Muramatsu-Kato et al, 2014 ), in a form of ontogenetic programming. HSD11B2 (16q22) protects cells from the growth-inhibiting and/or pro-apoptotic effects of cortisol, particularly during embryonic development.…”
Section: Genomic Foundation Of Basic Regulatory Mechanisms In Metsmentioning
confidence: 99%
“…Hydroxysteroid dehydrogenases 11β control the passage of glucocorticoids from the mother to the fetus. In humans, placental expression of HSD11β1 is associated with birth weight [ 44 ]; placental HSD11βs expression is reduced in SGA neonates [ 45 ]. Impaired placental insulin signaling is associated with obesity, gestational diabetes mellitus, or intrauterine growth restriction (IUGR) [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies did not report whether the tissue was collected uniformly from the medial or lateral segments of the placenta (Keleher et al, 2021;Mina et al, 2015;Räikkönen et al, 2014) although tissue inflammation has been shown to be more prone in the lateral sections (Burton et al, 2014). Likewise, three of the studies (Keleher et al, 2021;Mina et al, 2015;Muramatsu-Kato et al, 2014) did not report on the sampling time interval, increasing the risk that placental mRNA degradation could have interfered with the results (Burton et al, 2014;Freedman et al, 2021). Furthermore, in the Finish studies (Räikkönen et al, 2014), information on the pregnant women's nutritional habits was not reported, even though licorice, a common exposure in Finland (Räikkönen et al, 2009(Räikkönen et al, , 2010Strandberg et al, 2001), is a potent inhibitor of HSD11β2 and to some extent, an inhibitor of HSD11β1 (Chapman et al, 2013;Räikkönen et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%